Desain Augmented Reality Berbasis Cerita Ciung Wanara Dengan Metode Prototipe Di Karangkamulyan Kabupaten Ciamis - Zein, Zein Dity Aulia; Mulyana, Dadan; Sidiq, Maulana (Fakultas Teknik Jurusan Sistem Informasi Universitas Galuh, 2025)
The Karangkamulyan site in Ciamis Regency, as a historical relic of the Galuh Kingdom, faces challenges in maintaining its appeal to tourists in the digital age. The delivery of historical and cultural information, including the Ciung Wanara folk tale, is still conventional. This study aims to design an Augmented Reality (AR) application as an innovative solution with a focus on user interface (UI) and user experience (UX) design. The methods used in this study are prototyping with communication stages, rapid planning, rapid design modeling (UML), and prototype development using Figma. Interviews, observations, and literature studies were conducted to obtain data. The results of this research are the design of the admin system interface and tourist application that provide an interactive experience through AR. This prototype is expected to enhance the tourist experience while supporting the preservation of local culture at the Karangkamulyan Site.